Frauen in Furcht: Epiphanien, Zittern und der weibliche Körper im Markusevangelium - Neumann, Nils (Novum Testamentum, 2024)
Trembling with fear is a typically feminine phenomenon in the Gospel of Mark. The hermorrhaging woman as well as the women at the empty tomb tremble as they are afraid. Male characters, on the contrary, never tremble in Mark, although the male disciples frequently do exhibit fear. The present article explains these observations in the context of ancient medicine and philosophy of the body. Against this backdrop it is plausible that the women’s fearful trembling illustrates some form of embodied understanding of the divine presence that breaks into the earthly realm within the works of Jesus. This calls into question William Wrede’s contrasting juxtaposition of faith and fear in Mark.